Constitutional Legal Pluralism in Woe Balee Marriage: Between Custom, Shafi'i Jurisprudence, and State Law - Muhammad Haikal Tunisi (As-Siyasi: Journal of Constitutional Law, 2026)
The Woe Balee marriage tradition in Aceh reflects the interaction between Islamic jurisprudence, customary law, and the Indonesian legal system. Although widely accepted as a mechanism for preserving family continuity and protecting children after the death or dissolution of a marriage, the practice raises legal questions concerning the prohibition of marrying certain relatives, the relationship between living law and state law, and the constitutional protection of women’s and children’s rights through marriage registration. This study aims to examine the legal status of Woe Balee marriage according to Shafi'i jurisprudence and to analyze how the people of Gampong Blang Seunong understand and practice the tradition within the framework of Indonesian constitutional legal pluralism. The research employs an empirical socio-legal approach by combining normative analysis of classical Shafi'i legal texts, constitutional and statutory regulations, and the Compilation of Islamic Law with field data obtained through observation, semi-structured interviews, and document analysis involving village officials, religious leaders, customary leaders, and community members. The findings demonstrate that Woe Balee marriage is not absolutely prohibited under Shafi'i jurisprudence but is conditionally permissible after the legal dissolution of the previous marriage and the completion of the iddah period. Empirical evidence further indicates that the practice is primarily motivated by child welfare, family continuity, and social stability rather than customary obligation. However, unregistered marriages create legal uncertainty and weaken constitutional protection for women and children. The study concludes that constitutional recognition of customary practices should be accompanied by formal marriage registration to harmonize Islamic law, living law, and state law while ensuring legal certainty and the effective protection of fundamental rights